Des récits régionalistes à la télévision - Licia Soares de Souza (Communication)
The author exposes a methodology which aims to compare Québécois and Brazilian televised fiction which has been adapted from regionalist novels. Taking as its starting point the analysis of intertextual scenarios, she describes the way that writing for television transforms literary narratives and, by observing transtextual scenarios, she shows the manner in which televised fiction dialogues with current events. Because of the many cross sections between the two types of scenarios, Brazilian and Québécois televisual productions, notwithstanding the different contexts in which they evolve, both possess aesthetic particularities which are distinct from the melodramatic models which circulate in the Americas.